Frequency of Hyponatremia in Children Admitted with Pneumonia - Adnan, Mian Sohail; Bibi, Nafeesa Bibi; Noor Ul Bashar; Anees, Aleena Anees; Zahid, Masroor; Khan, Muhammad Sohaib (Indus Journal of Bioscience Research, 2025)
Objectives: The purpose of this study was to establish the prevalence of hyponatremia among children of 2 months to 5 years of age admitted at Ayub Teaching Hospital, Abbottabad, with pneumonia and factors related to it. Materials and Methods: An analytical cross-sectional study was conducted in the pediatric department on 135 children with pneumonia. The level of hyponatremia was determined by the patient’s serum sodium concentration